Association of Kidney Function, Vitamin D Deficiency, and Circulating Markers of Mineral and Bone Disorders in CKD - Ureña-Torres, Pablo; Metzger, Marie; Haymann, Jean Philippe; Karras, Alexandre; Boffa, Jean-Jacques; Flamant, Martin; Vrtovsnik, François; Gauci, Cédric; Froissart, Marc; Houillier, Pascal; Stengel, Bénédicte (American journal of kidney diseases, 2011)
Vitamin D (25 hydroxyvitamin D [25(OH)D]) deficiency is common in patients with chronic kidney disease (CKD). Neither the relation of this deficiency to the decrease in glomerular filtration rate (GFR) nor the effects on CKD mineral and bone disorders (MBD) are clearly established. Cross-sectional analysis of baseline data from a prospective cohort, the NephroTest Study. 1,026 adult patients with all-stage CKD not on dialysis therapy or receiving vitamin D supplementation. For part 1, measured GFR (mGFR) using 51Cr-EDTA renal clearance; for part 2, 25(OH)D deficiency at <15 ng/mL. For part 1, 25(OH)D deficiency and several circulating MBD markers; for part 2, circulating MBD markers. For part 1, the prevalence of 25(OH)D deficiency was associated inversely with mGFR, ranging from 28%-51% for mGFR ≥60-<15 mL/min/1.73 m 2. It was higher in patients of African origin; those with obesity, diabetes, hypertension, macroalbuminuria, and hypoalbuminemia; and during winter. After adjusting for these factors, ORs for 25(OH)D deficiency increased from 1.4 (95% CI, 0.9-2.3) to 1.4 (95% CI, 0.9-2.1), 1.7 (95% CI, 1.1-2.7), and 1.9 (95% CI, 1.1-3.6) as mGFR decreased from 45-59 to 30-44, 15-29, and <15 (reference, ≥60) mL/min/1.73 m 2 ( P for trend = 0.02). For part 2, 25(OH)D deficiency was associated with higher age-, sex-, and mGFR-adjusted ORs of ionized calcium level <1.10 mmol/L (2.6; 95% CI, 1.2-5.9), 1,25 dihydroxyvitamin D concentration <16.7 pg/mL (1.8; 95% CI, 1.3-2.4), hyperparathyroidism (1.8; 95% CI, 1.3-2.4), and serum C-terminal cross-linked collagen type I telopeptides concentration >1,000 pg/mL (1.6; 95% CI, 1.0-2.6). It was not associated with hyperphosphatemia (phosphate >1.38 mmol/L). Cross-sectional analysis of the data prevents causal inferences. 25(OH)D deficiency is related independently to impaired mGFR. Both mGFR decrease and 25(OH)D deficiency are associated with abnormal levels of circulating MBD biomarkers.